Meshless Analysis of an Embankment Using Local Galerkin Radial Point Interpolation Method (LGRPIM) - Juraj Muzik; Karel Kovarik; Dana Sitanyiova (Communications - Scientific letters of the University of Zilina, 2013)
The paper deals with use of the meshless method for slope stability analysis. There are many formulations of the meshless methods. The article presents the Local Galerkin Radial Point Interpolation method (LGRPIM) – local weak formulation of the equilibrium equations. The main difference between meshless methods and the conventional finite element method (FEM) is that meshless shape functions are constructed using randomly scattered set of points without any relation between points. The shape function construction is the crucial part of the meshless numerical analysis in the construction of shape functions. The article presents the radial point interpolation method (RPIM) for the shape functions construction. The numerical example of the slope stability was calculated using meshless computer code and compared with FEM results.